Likuiditas dan Ukuran Perusahaan pada Kebijakan Dividen di Perusahaan yang Terdaftar Bursa Efek Indonesia Tahun 2017-2021 - Mesi Muraliza; Lidya Martha (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to examine the liquidity and size of the company on dividend policy in companies listed on the Indonesian Stock Exchange. The research population is all companies listed on the IDX for the 2017-2021 period. The sample was selected using the purposive sampling method with the sample criteria being companies listed on the IDX in the 2017-2021 period, companies with complete financial reports in the 2017-2021 period, companies paying dividends in the 2017-2021 period, and a sample of 45 companies was obtained. The data source is the company's annual financial report taken through the official website of the Indonesian stock exchange (www.idx.co.id). The test uses multiple linear regression analysis with the Eviews program tool. Liquidity is measured using the Current Ratio, while company size is measured using Size and dividend policy is measured by the dividend payout ratio. The results showed that the variable liquidity had a positive and significant effect on dividend policy, while firm size had a negative and insignificant effect on dividend policy.